Forest Plundering in the Forest Management Unit (KPH) Randublatung, Blora Regency: Types of Plundering and the Involvement of External Community Actors - Ulyatin, Nazal Chilmi; Sulistiyono, Singgih Tri; Rochwulaningsih, Yety (Indonesian Historical Studies, 2024)
This study examines forest plundering in KPH Randublatung involving individuals from outside the forest communities. The Reformation era marked the beginning of numerous demonstrations in both urban and rural areas across various regions. In forest villages where communities have close geographical proximity to state forests, one form of particularly intense demonstration was forest plundering. As residents of forest villages, or communities living near KPH, they have engaged in the practice of mblandongeven since the colonial period. Acts of taking wood from state forests have occurred for a long time. However, in the lead-up to the Reformation, taking wood from the forest evolved beyond mere theft, escalating into acts of plundering. This study analyzes the factors driving forest plundering, which also involved parties from outside the forest villages. The research findings indicate both internal (village community) and external factors contributing to the plundering. Internal factors include community customs, perceptions, and the necessity for survival amidst an environment that does not guarantee livelihood sustainability. External factors include political instability in the lead-up to the Reformation, which created opportunities for plunderers due to the absence of legal certainty. Additionally, the emergence of financiers driven by the demand for teak wood in the market also fueled organized and structured plundering. These actions were often supported by security forces.